The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1080/10538712.2010.495700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Student Vulnerability on Perceptions of Teacher–Student Sexual Involvement

Abstract: This study explored whether the vulnerability of an adolescent student affected perceptions of teacher sexual misconduct. Respondents (150 male and 150 female undergraduates) read scenarios depicting teacher sexual misconduct varied by respondent gender, gender dyad (male teacher-female student and female teacher-male student), and three levels of student vulnerability. The vulnerability of the student was found to have little impact on perceptions. On most variables, interactions emerged between respondent ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…This finding is consistent with previous research (e.g., Dollar et al, 2004;Fromuth & Holt, 2008). Gender role stereotypes and sexual scripts postulate that a sexual relationship between a female adult and a male adolescent is viewed as least abusive and most normative compared with the three other teacher-student gender dyads, thereby leading to a greater acceptance of such sexual relationships (Broussard et al, 1991;Dollar et al, 2004) especially by male participants (Fromuth & Holt, 2008;Fromuth et al, 2013;Fromuth et al, 2010). Some researchers have suggested that sexual encounters between female adults and male adolescents are valued (and even coveted) as "status-enhancing" sexual learning experiences (Broussard et al, 1991;Nelson & Oliver, 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with previous research (e.g., Dollar et al, 2004;Fromuth & Holt, 2008). Gender role stereotypes and sexual scripts postulate that a sexual relationship between a female adult and a male adolescent is viewed as least abusive and most normative compared with the three other teacher-student gender dyads, thereby leading to a greater acceptance of such sexual relationships (Broussard et al, 1991;Dollar et al, 2004) especially by male participants (Fromuth & Holt, 2008;Fromuth et al, 2013;Fromuth et al, 2010). Some researchers have suggested that sexual encounters between female adults and male adolescents are valued (and even coveted) as "status-enhancing" sexual learning experiences (Broussard et al, 1991;Nelson & Oliver, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Female mock jurors are more likely to believe the child complainant's allegation (Bottoms, Golding, Stevenson, Wiley, & Yozwiak, 2007;Quas et al, 2002) and are more in favor of a conviction decision (Bottoms et al, 2007;Crowley, O'Callaghan, & Ball, 1994;Gabora, Spanos, & Joab, 1993;Quas et al, 2002) compared with male mock jurors. A few studies have explored participant gender in teacher-student relationships (e.g., Broussard et al, 1991;Fromuth & Holt, 2008;Fromuth, Kelly, Wilson, Finch, & Scruggs, 2013;Fromuth, Mackey, & Wilson, 2010). Consistent with the other CSA research, Broussard et al (1991) found that women generally held more pro-victim attitudes than men.…”
Section: The Role Of Juror Characteristics On Perceptions Of Teacher-supporting
confidence: 57%
“…For example, based on a summary of the research in seven studies, Shakeshaft (2004) reported that from 4% to 43% of educator abusers are female(s). Indeed, it should be noted that the proportion of female and male educator abusers targeting male students are very likely to be underreported, as males are socialized to feel appreciation of sexual interest from females (Fromuth, Mackey, & Wilson, 2010; Gallagher, 2000; Ratliff & Watson, 2014) and to be wary of reporting same sex encounters (Shakeshaft, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the limited research on educator misconduct that exists, most focuses on sexual abuse: its prevalence and students' vulnerability (Fromuth et al, 2010;Shakeshaft, 2004;Simpson, 2010), descriptions of sexual abusers (Ratliff and Watson, 2014), perceptions of teacher-student sexual relationships (Fromuth et al, 2010;Bryant, 1993), and strategies to protect children from predators (Knoll, 2010;Ratliff and Watson, 2014;Shakeshaft, 2004). This is understandable, as sexual deviance is the biggest concern of parents and administrators.…”
Section: Literature Reviewmentioning
confidence: 99%